Predictive impact of previous coronary artery bypass grafting on mortality after MitraClip implantation for ischemic functional mitral regurgitation. (15th June 2019) - Kitamura, Mitsunobu; Kaneko, Hidehiro; Schlüter, Michael; Schewel, Dimitry; Schmidt, Tobias; Alessandrini, Hannes; Kreidel, Felix; Okamoto, Maki; Neuss, Michael; Butter, Christian; Kuck, Karl-Heinz; Frerker, Christian
Abstract: Background: Many candidates with ischaemic functional mitral regurgitation (FMR) have previously undergone coronary artery bypass grafting (CABG), in which transcatheter mitral valve repair can be reasonable for ameliorating the deteriorated hemodynamic and heart failure symptoms. We sought to elucidate the outcomes of MitraClip (MC) implantation in patients with symptomatic ischaemic FMR after CABG. Methods: We investigated clinical characteristics, outcomes and predictive impact of previous CABG on mortality in ischaemic FMR patients who underwent MC implantation from two high-volume centres in Germany. Results: We enrolled 159 patients who previously underwent CABG. Compared with a reference group that did not previously undergo CABG ( n = 182), the cohort consisted of more elderly patients (75.0, standard deviation [SD] 7.7 versus 72.9, SD 9.6 years, p = 0.028), more men (84% vs. 69%, p < 0.001), and reduced tricuspid annular plane systolic excursion (14.0, SD 4.0, vs. 16.6, SD 4.6 mm, p < 0.0001). The CABG group showed similar outcomes regarding procedural success (91% vs. 94%, p = 0.24) and 30-day mortality (5.0% vs. 6.0%, p = 0.68), but worse survival after MC implantation (log-rank p = 0.019, hazard ratio 1.56 [95% confidence interval (CI) 1.08–2.26]). After propensity score matching ( n = 224), the hazard ratio was 1.18 [95%CI 0.76–1.84] without statistical significance ( p = 0.46). Conclusions: Transcatheter mitral valve repair using the MC is a viable treatment option for patients with symptomatic ischaemic FMR after CABG. Although the baseline characteristics seemed to point to sick patients, CABG itself had only a modest impact on survival. Highlights: Ischaemic functional mitral regurgitation is the most often in MitraClip candidates. 47% in ischaemic functional mitral regurgitation had previous coronary bypass. Short-term result of MitraClip was similar regardless of previous coronary bypass. Previous coronary bypass had a modest adverse impact on survival after MitraClip. MitraClip is a viable treatment for patients with previous coronary bypass.